Letters from Konstantin Golubov to Nikolay Ogarev: an attempt of linguostylistic analysis: Письма Константина Голубова Н. П. Огареву: попытка линвостилистического анализа - Pociechina, Helena (Przegląd Wschodnioeuropejski, 2020)
This article is part of a general study of the book collection of the former Fedoseevsky Holy Trinity and Saviour Monastery, located in Voinovo (currently Poland, formerly East Prussia). The author of the article presents a description of the content and style characterization of the open letters addressed from the Old-Believers publisher and writer Konstantin Golubov to a collaborator of the printing house Free Russian Press in London, the famous Russian poet, historian and political activist N. P. Ogarev. The letters were published in the third book of the religious-philosophical journal “Truth” (1868), which was published by Golubev in his own Slavic Press in Johannisburg (currently Pisz).